PERANCANGAN SISTEM PENENTUAN SIMILARITY KODE PROGRAM PADA BAHASA C DAN PASCAL DENGAN MENGGUNAKAN ALGORITMA RABIN-KARP - Surahman, Ade Mirza (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
This research aims to design and implement an application that can determine the percentage of similarity to the C code and post using Rabin-Karp algorithm. In this application the input use is a code C and Pascal who type *. C and *. Pas, while the output of the application is in the form of percentage similarity of both the tested code and the processing time required in each process. The results of this study are called "Similarty Checked" is developed using Borland Delphi 7. This application can determine the percentage of similarity of code under test. On the application of "Similarity Checked", there are 5 stages of a process called preprocessing to prepare the program code before checking the similarity of two documents, that are: case folding, filtering, parsing, k-gram, hashing and two-stage process to obtain the percentage of similarity checking code ie: checking the rabin-Karp algorithm and determination of the value of similarity calculated by dice similarity coeficients. Testing is done by trying out some of the code C and Pascal programs are different, and by using k-gram values ??are different. Based on the testing that has been done, showed that the application has been designed to determine the percentage of similarity of code C and Pascal programs were tested.Â Â